2017
DOI: 10.1111/imig.12366
|View full text |Cite
|
Sign up to set email alerts
|

Daring ‘life‐return projects’ to post‐Dayton Bosnia and Herzegovina

Abstract: This article discusses the prospects for realization of rights-based return against the backdrop of a twenty years-long (inter)nationally managed return process to post-Dayton Bosnia and Herzegovina. It draws on 42 in-depth interviews with two different waves of returnees: early assisted returns (1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005), and later self-organised returns (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013). Our findings show that realization of return implicates the courageous we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…I did not find any proof of ongoing monitoring that had been carried out by the international and national bodies. A similar mix of complaints, disillusionment, and frustration among Bosnian repatriates has been discussed by other scholars (Porobić 2017;Jansen 2007a;Hovey 2001).…”
Section: The Successful Minority Return and Limitations Of Its Measursupporting
confidence: 70%
See 1 more Smart Citation
“…I did not find any proof of ongoing monitoring that had been carried out by the international and national bodies. A similar mix of complaints, disillusionment, and frustration among Bosnian repatriates has been discussed by other scholars (Porobić 2017;Jansen 2007a;Hovey 2001).…”
Section: The Successful Minority Return and Limitations Of Its Measursupporting
confidence: 70%
“…These authors also state that it remains open for debate whether the notion of the "sustainability" of return represents the best way of conceptualizing the success of a return process (Black & Gent 2006). In any event, official numbers cannot adequately depict any individual's difficulties with the repatriation process (Porobić 2017).…”
Section: The Successful Minority Return and Limitations Of Its Measurmentioning
confidence: 99%
“…We find support for the social capital hypothesis as well. Related qualitative studies in Turkey (Çelik, ), Ukraine (Nikolko and Carment, ) and Bosnia (Belloni, ; Porobic, ) point to the role of community effort, yet ours is one of the first quantitative studies to demonstrate the complex relationship between the community variable and voluntary return. As expected, forced migrants from rural areas are more likely to desire community return and to return as a community.…”
Section: Discussion: Reversing Forced Migration In Bosnia and Beyondmentioning
confidence: 76%
“…As Porter and Haslam record [ 19 ], institutional accommodation in post-displacement situations tends to have a strong and negative impact on health outcomes. Further, Porobić has found that, while displacement generates threats to the well-being of refugees, social interventions and collective responses may in fact mitigate the experience of trauma and promote better health [ 20 ]. Evaluations of health conditions inside reception centres may therefore inform the delivery of humanitarian assistance and ease integration in the host state.…”
Section: Introductionmentioning
confidence: 99%